Citrus sanitation methods for the elimination of Citrus tristeza virus (CTV) - Meziane M.; Frasheri D.; Carra A.; Djelouah K.; Carimi F.; D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
The use of healthy propagating material is of utmost importance in the control of CTV, which is the most serious virus affecting citrus trees worldwide. All the sanitation methods available are effective in CTV elimination; shoot-tip-grafting (STG) and somatic embryogenesis from stigma and style in vitro culture (SE) are the preferred ones for their numerous advantages. Both techniques are successful in regenerating CTV-free plants, identical to the mother tree, and they can also be applied in the safe international exchange of citrus healthy germplasm. SE is user friendly and can be extensively applied to all Citrus species whenever suitable explants are available; while STG can be applied in the sanitation of clementines and pomelos, which are not regenerated by SE.